Fetal Bladder Rupture as a Complication of Adjunctive Therapy in Severe Maternal SARS-CoV-2 Pneumonia. (3rd September 2022) - Gutierrez, Jorge; Sepulveda, Waldo; Ramirez, Raul; Acosta, Gina; Ambiado, Sergio
Abstract: Introduction: A case of spontaneous fetal bladder rupture occurring in a woman with SARS-CoV-2 pneumonia receiving invasive ventilatory support is reported. Case: A 33-year-old woman was admitted at 30.6 weeks' gestation with the diagnosis of severe pneumonia due to COVID-19. The patient required invasive mechanical ventilation on day 2. Propofol, fentanyl, midazolam, and dexmedetomidine were administered for sedation, pain relief, and to improve patient-ventilator interaction. A bedside ultrasound on day 3 revealed fetal megacystis. Follow-up scan two days later showed urinary ascites and a collapsed bladder. The diagnosis of fetal bladder rupture was confirmed postpartum. Bladder repair was performed on day 5, with an uneventful recovery. Discussion: Transplacental transfer of opioids during invasive ventilatory support in pregnancy may cause acute fetal bladder atony leading to severe urine retention and, potentially, bladder rupture. This can be a serious complication of adjunctive therapy in women with severe SARS-CoV-2 pneumonia.